Effectiveness Health education based on Behavioral theory of change Public health behavior: Sistematic Literature Review - Eliseba Borges Ximenes; Levi Anatolia S.M. Exposto; Aguida Araujo de Andrade; Linésia Muki C. O. F. Pinto; Josefa Leandra da Costa; Florindo da Silva Vicente (YCMM, 2026)
Introduction : A strategic initiative to enhance the attainment of optimal health status is improving public health behavior. Research shows that health education initiatives can increase self-efficacy and community preparedness for disasters, both of which are critical to encouraging lasting behavior change. Public health education is not only information, but also a systematic effort to change individual and community attitudes and behaviors to promote and prevent health systems at the national and global levels. Objective : Of this study to analyze how health education based on behavioral theory can alter public health behavior. Metodu: Systematic Literature Review (SLR) approach, utilizing PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were obtained from three scientific databases : Google Scholar, PubMed, ScienceDirect, from 2021-2026 total 50 articles. Results : Educational interventions based on the behavioral theories of Health Belief Model (HBM), Social Cognitive Theory (SCT), Theory of Planned Behavior (TPB), and Behavior Regulation Theory (BRT) are important public health strategies to change population behavior. Education not only enhances knowledge, but also influences psychosocial constructs such as attitude, self-efficacy, and risk perception, which play a major role in determining health behavior. However, evidence also shows that education alone is not sufficient, as social and environmental barriers such as lack of time, routine, and social support continue to be major obstacles. Conclusion : Theory-based education is effective in initiating behavior change, but to achieve lasting population impact, an integrated approach that considers individual, social, and environmental factors is needed.